Life Cycle Assessment in the Air Transport System - Kan, D.M.; Scheers, E.; Paletti, L.; Rahn, A.; Bachman, J.; Albano, J.; Höller, M.; Diniz, S.; Kroos, K. (NLR, DLR, 2025)
This document serves as guidelines for Life Cycle Assessment (LCA) in the air transport system. This includes aircraft manufacturing, use, and end-of-life, the fuel or energy source supply chain, and airport infrastructure and operations, encompassing all components and processes involved in air transport. The content is based on joint DLR-NLR knowledge of air transport and LCA. The objective of the guidance is to facilitate consistent and credible assessment and communication of the environmental life cycle impact of products, assets and part of the air transport system, providing state-of-the-art guidance for the people working in aviation. Specifically, this guidance is meant to: • Ease the process of conducting LCA in the air transport system; • Build on the best available scientific knowledge and methods; • Facilitate consistency with the ISO 14040-14044 standards on LCA; • Seek alignment with potential forthcoming Product Environmental Footprint Category Rules (PEFCR) guidance; • Serve as reference work for LCA practitioners; • Provide support for decision-making by leveraging LCAs of air transport systems. The guidance is targeted at researchers and companies seeking to evaluate the environmental impact of: the entire air transport system, including electricity / fuel production, aircraft production; airport infrastructure, operations, maintenance and end-of-life; The life cycle of specific parts of the air transport system. Specific target audiences are research institutes and academia in the aviation sector; LCA practitioners active in the aviation industry conducting product assessments and sharing results with value chain partners; Stakeholders utilizing LCA results to inform (business and policy) decisions; Value chain stakeholders requiring insight into the assumptions underlying environmental product claims, to prepare for upcoming legislation. This approach builds on the ISO 14040-14044 standards on LCA. A more detailed approach than the ISO standards is needed for two reasons. First, the ISO standards include steps, definitions and modelling choices, but leave a large degree of freedom to the LCA practitioner. To make results better comparable between studies, harmonisation in the approach is needed. Second, the aviation sector faces specific modelling challenges, for which methodological solutions are needed. The document offers aviation-specific guidance, building on existing standards. The approach proposed in this document is the result of literature review of existing generic LCA standards (ISO 14040-14044, PEF, EN15804), existing LCA standards for aviation such as the Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) Life Cycle Assessment Methodology, peer reviewed LCA studies, and internal discussions between LCA researchers in DLR and NLR. No formal stakeholder consultation process and no consensus building procedure has taken place. Rather, this document can serve as an input or starting point to create a formalised LCA standard for aviation. As the interest in, and knowledge of LCA in the air transport system is evolving, this guidance document should be updated or aid official standardisation activities. The content of this document is structured around the four phases of Life Cycle Assessment (LCA) as defined in the relevant international standards. Chapter 2: Goal and Scope of LCA in the air transport system establishes the purpose of the study, product(s) to be studied, the function and functional unit, the system boundaries, and other methodological choices. Chapter 3: Life Cycle Inventory Analysis involves collecting data on all relevant inputs and outputs, such as energy use, emissions, and material flows across the system. Chapter 4: Life Cycle Impact Assessment (LCIA) translates these inventory data into potential environmental impacts, such as climate change, resource depletion, acidification, and fine particulate matter formation. Chapter 5: Interpretation integrates the findings, evaluates their significance, and provides recommendations to support informed decision-making. Chapter 6: LCA Across Different Use-Cases presents different use cases to illustrate the application of LCA in the air transport sector. Chapter 7: References provides the overview of references to literature, the list of abbreviations, and the lists of figures and tables All seven chapters include definitions of the methodological choices, a literature review of LCA studies and international standards, and proposals for methodological choices for LCA in the air transport system. The guidance can be used for LCA on the air transport system as a whole (including maintenance and flight operations, electricity and aviation fuels, aircraft materials, aircraft components, aircraft, airport infrastructure and operations).
Guidance Document